DETERMINING THE IMPACT OF VOLCANIC ERUPTION ON THE DISCHARGE USING HYDROLOGICAL MODEL Case in Code Watershed, Yogyakarta Special Province, Indonesia - , AGUS YASIN; , Dr. M. Pramono Hadi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
After Merapi eruption (October â December 2010), several conditions change as consequence of the eruption. This research analyzed the hydrologic change of the Code watershed (30 km2) in north Yogyakarta. Therefore this research developed a hydrologic model for the watershed by means of available data and hydrological equations to predict the discharge and further simulate the extreme rainfall event to predict flood in Code river. The research concluded that the changes related to hydrological process in Code watershed due to the eruption is mainly affected the soil. The change includes: sand fraction increased on soil texture composition, additional ash deposition of 32-41 mm on soil depth, and decreased of infiltration rates. Related with the model, statistically it has high error and low correlation of 0.46 and 0.22 for pre and post eruption model respectively. The model simulated that soil depth has the most sensitive to the discharge. It performs positive response while the other parameters tested, Ksat, porosity and maximum storage gives negative response to the discharge. In addition, the amount of discharge in the model is lower than the amount in measured discharge for the pre eruption model. Meanwhile, the post eruption model performs higher than the measured discharge. Predicted discharge based on extreme rainfall event on 5, 20, 50 and 100 year periods gives the amount of discharge in a day reaching 2,171,967 m3/day, 2,969,264 m3/day, and 3,515,760 m3/day respectively. About 19, 29, 35 and 37 of 50 sections of Code river were prone to flood when 5, 20, 50 and 100 year extreme rainfall event occurs respectively. Sub disctrics that prone to flood are Jetis, Gondokusuman, Gedong tengah and Mergangsan.